Técnica de criação e associação de métodos de controle da broca-do-café, Hypothenemus hampei (Ferrari) - Celestino, Flávio Neves (2014)
The coffee berry borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) is largely responsible for losses caused to the coffee culture. Thus, it has been sought alternatives for the control of this pest, such as the botanical insecti